Carl Nielsen and the Gothenburg Orchestral Society 1914-31. Contact, Programming, and Repertoire - Hauge, Peter (Carl Nielsen Studies, 2005)
During his marital crisis, which started around 1917, Nielsen tried to get away from Copenhagen where he found the conditions gradually becoming more and more difficult. When he realised that Wilhelm Stenhammar – chief conductor in Gothenburg – wanted to spend more time on composing Nielsen wrote several times asking whether he could act as a substitute for Stenhammar. They agreed that Nielsen should relieve Stenhammar of some of the duties as conductor, initially just for one season. However, the Orchestral Society was so satisfied with Nielsen — and he with the conditions in Gothenburg — that he worked as a substitue for many years. Apparently Nielsen was able to decide which works to include in the programmes, as long as he followed the Society’s guidelines. From a modern point of view, the programming may seem somewhat haphazard and impulsive but it was often dictated by many practical circumstances. Nielsen’s repertoire in Gothenburg seems conservative and not as varied as that of younger conductors, and he does not seem to have had a particular interest in new musical trends. The article includes an appendix containing the programmes of those concerts which Nielsen conducted in Gothenburg.